Elucidating the chemical state of elements in CaO-CuO-CeO2 mixed oxide by X-ray photoelectron spectroscopy - Son, Pham Anh; Huong Hue, Hoang Thi (Vietnam Journal of Chemistry, 2017)
In this research, three-component-oxide CaO-CuO-CeO2 was fabricated a sol-gel method. This mixed oxide acted as the catalysts for the complete oxidation of phenol in the presence of hydro peroxide. The activity of the catalyst was monitored versus fabrication conditions of mixed oxide such as aging temperature, calcination temperature and time. Under the optimum conditions including aging temperature at 70 oC, calcination at 600 oC for 30 min, the catalyst gave the best activity with 96.3% phenol conversion. Among tested mixed oxides or single oxides, three-component-oxide CaO-CuO-CeO2 exhibited the highest performance. The chemical state of metal elements in the mixed oxide was carefully studied by high-resolution X-ray photoelectron spectroscopy (XPS) technique. The XPS spectra of Ca 2p, Cu 2p, and Ce 3d were recorded in ranges of 935-965, 927-967, and 878-930 eV, respectively. The curve fitting processes were carried out on CasaXPS version 2.3.18PR1.0 software with Shirley or Tougaard background and GL(m) line shape. Some constraints such as the FWHM, splitting energy and peak area ratio of spin-orbit interaction were introduced into the fitting process in order to achieve the highest physical meaning of the spectrum deconvolution. The fitting result proved the coexistence of Ce4+, Ce3+, Cu2+ and Cu+ in the component of the prepared material. The formation of Ce3+ and Cu+ from the interaction between Ce4+ and Cu2+ accompanied the appearance of oxygen vacancies in the crystal structure of CeO2 support. That process was enhanced by the presence of calcium element. Oxygen vacancies played important role in the formation of superoxide anions that were the highly active intermediate for the phenol oxidation. Keywords. X-ray photoelectron spectroscopy, binding energy, chemical state, CaO-CuO-CeO2, phenol oxidation.